The dual-detection mode and improved photoresponse of IGZO-based photodetectors by interfacing with water-soluble biomaterials. (11th June 2022) - Feria, Denice N; Hsu, Feng-Hsuan; Chan, Yi-Chieh; Chen, Bo-Rui; Wu, Chang-Jer; Lin, Tai-Yuan
Abstract: The use of conventional fabrication methods rapidly developed the performance and notable enhancements of optoelectronic devices. However, it proved challenging to develop and demonstrate stable optoelectronic devices with biodegradability and biocompatibility properties towards sustainable development and extensive applications. This study incorporates a water-soluble Cr-phycoerythrin (Cr-PE) biomaterial to observe its optical and electronic properties effects on the pristine indium gallium zinc oxide (IGZO)-based photodetector. The fabricated photodetector demonstrates an extended absorption detection region, enhanced optoelectronic performance, and switchable function properties. The resulting photocurrent and responsivity of the IGZO/Cr-PE structure have increased by 5.7 and 7.1 times as compared to the pristine IGZO photodetector. It was also observed that the photodetector could operate in UV and UV–visible with enhanced optical properties by effectively adding the water-soluble Cr-PE. Also, the sensing region of IGZO photodetector becomes changeable. It exhibits switchable dual detection by alternatively dripping and removing the Cr-PE on the IGZO layer. Different measurement parameters such as detectivity, repeatability, and sensitivity are highlighted to effectively prove the advantage of including Cr-PE on the photodetector structure. This study contributes to understanding the potential functions in improving optoelectronic devices through an environmental-friendly method.